(untitled) (Annals of Medical Research, 2021)
Aim: To make a demographic analysis of patients operated on because of skin cancer in the last ten years in the Diyarbakir region of Turkey. Information was mapped related to age, gender, localization, grade, and size of skin cancers other than melanoma.Material and Methods: A retrospective examination was made of patient data in the computerized information system from the last ten years. Age and gender of the relevant patients, tumour diagnosis, size, and localization were recorded. Results: From the archive scan, the data of 733 patients were retrieved. The diagnosis was basal cell carcinoma (BCC) in 540 cases, squamous cell carcinoma (SCC) in 154, and basosquamous cell carcinoma (BSCC) in 32. BCC was determined more in males (M/F:280/260), localization was mostly in the nasal region and it was seen most in the 60-70 years age range. SCC was diagnosed more in males (M/F:92/62) in the 70-80 years age group, and the most common localization was on the cheek. BSCC was observed more often in females (M/F:14/18). Conclusion: Diyarbakir is geographically located in the South-east Anatolian region of Turkey, those who live there are exposed to long hours of intense sunlight in certain months of the year. In this region, BCC and SCC were seen more in males and BSCC was determined more in females. When it is considered that UV exposure is significant in the etiology of skin cancers, it can be concluded that characteristics change according to geographic region and epidemiological characteristics (skin type, genetic factors, regional working conditions).